Femtosecond Transient Absorption Microspectroscopy of Benzil Confined Into a Single Bead of Porous Glass. Issue 3 (1996) - Porter, Christopher F.; Tamai, Naoto; Masuhara, Hiroshi
Abstract : The photophysical properties of benzil dissolved in free solution and in solution confined into a single bead of porous glasses (size < 100 μm) were investigated by femtosecond transient absorption microspectroscopy. In nonpolar solvent, cyclohexane, the rate of conformational change from the skewed to the near trans-planar form was reduced from 2.2 × 10 12 s -1 in free solution to 9.1 × 10 11 s -1 in porous glasses with an average pore diameter of 26 nm. In polar solvent, DMF, however, there was little difference between the two systems.